Assessment of the axisymmetric load acting on the bogie frame of a wagon during derailment - G. I. Gadzhimetov (Вестник Научно-исследовательского института железнодорожного транспорта)
Introduction. The authors describe the practice of checking newly built cars to assess their durability, taking into account the ultimate operating loads and their application schemes stipulated in the regulatory documents. Axisymmetric loads are not part of the bogie frame static strength assessment rules. For mechanical safety reasons, the presence of residual frame deformation asymmetry is not permitted. All-welded bogie frames are particularly prone to axisymmetric loads. It confirms the need for refinement of design methods to ensure reliability and safety of cars in service.Materials and methods. Methods of computational analysis and computer modelling were used to determine the loading scheme and the magnitude of the axisymmetric load; experimental work was carried out on a passenger carriage with two-axle bogies and an all-welded frame in which the side beams are rigidly connected by cross beams.Results. An additional type of derailment is justified, which is relevant for the operation of wagons with all-welded bogie frames. The load pattern of the bogie frame and the magnitudes of the load applied to the frame for the mode of operation in which the static strength of the frame is to be assessed are determined.Discussion and conclusions. In the event of a wheel derailment, the all-welded bogie frame is subjected to maximum axisymmetric loads, which could lead to axisymmetric deformation and frame failure. The all-welded bogie frame should be assessed for static strength in derailment mode. The overload coefficients are justified. The reliability of the bogie frame in service and the safety of the traffic could be improved by developing, calculating and evaluating the design with the additional mode mentioned above.